ALLELIC VARIATIONS OF SOS, HVNHX AND SDO GENES IN SOME BARLEY (Hordeum Vulgare L.) GENOTYPES - Taher, D.; AL-Aouda, A.; Lawand, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study has been carried out at the Biotechnology Lab., Department of Field Crops, Faculty of Agriculture, Damascus University during the growing season 2019 - 2020, in order to detect the variations of SOS, HVNHX and SDO genes in different barley genotypes.  Clear variations in the SOS, HVNHX and SDO genes, which are responsible for salinity tolerance were found among the investigated genotypes. It has been found that the variation in the amplicon size between loci per gene was very high in some cases, while there was a high degree of symmetry in other cases, and could be easily distinguished on 2% Agarose gel. The PCR results for the SOS genes (SOS1, SOS2, SOS3), HVNHX genes (HVNHX1, HVNHX2, HVNHX3) and SDO genes (Cu/Zn SODII, Cu/Zn SODI, CAT, GRI , APXIII) have shown only one morphological pattern in most of the studied genotypes, while revealed two patterns for the SOS3 gene, but the rest of genes (HVNHX1, HVNHX2, HVNHX3  Cu/Zn SODI, CAT) exhibited only one morphological pattern. The SOS3 was superior in the number of polymorphic patterns, as the number of total patterns was 14 in all the studied genotypes, but the Cu/Zn SODI showed the least number of polymorphic patterns with only 1 pattern, while the largest number (7 patterns) was detected in the genotype (H9), but the two genotypes Fourat9 and Fourat7 showed only one polymorphic pattern.